CAMP‐Induced Nuclear Condensation of CRTC2 Promotes Transcription Elongation and Cystogenesis in Autosomal Dominant Polycystic Kidney Disease. Issue 10 (17th January 2022) - Mi, Zeyun; Song, Yandong; Wang, Jiuchen; Liu, Zhiheng; Cao, Xinyi; Dang, Lin; Lu, Yumei; Sun, Yongzhan; Xiong, Hui; Zhang, Lirong; Chen, Yupeng
Abstract: Formation of biomolecular condensates by phase separation has recently emerged as a new principle for regulating gene expression in response to extracellular signaling. However, the molecular mechanisms underlying the coupling of signal transduction and gene activation through condensate formation, and how dysregulation of these mechanisms contributes to disease progression, remain elusive. Here, the authors report that CREB‐regulated transcription coactivator 2 (CRTC2) translocates to the nucleus and forms phase‐separated condensates upon activation of cAMP signaling. They show that intranuclear CRTC2 interacts with positive transcription elongation factor b (P‐TEFb) and activates P‐TEFb by disrupting the inhibitory 7SK snRNP complex. Aberrantly elevated cAMP signaling plays central roles in the development of autosomal dominant polycystic kidney disease (ADPKD). They find that CRTC2 localizes to the nucleus and forms condensates in cystic epithelial cells of both mouse and human ADPKD kidneys. Genetic depletion of CRTC2 suppresses cyst growth in an orthologous ADPKD mouse model. Using integrative transcriptomic and cistromic analyses, they identify CRTC2‐regulated cystogenesis‐associated genes, whose activation depends on CRTC2 condensate‐facilitated P‐TEFb recruitment and the release of paused RNA polymerase II. Together, their findings elucidate a mechanism by which CRTC2 nuclear condensation conveys cAMP signaling to transcription elongation activation and thereby promotes cystogenesis in ADPKD. Abstract : Biomolecular condensates play key roles in controlling gene expression in response to internal and external signals. This study elucidates a mechanism by which CRTC2 nuclear condensation conveys cAMP signaling to transcription elongation activation and cystogenesis in autosomal dominant polycystic kidney disease.